English Learning Using Infographics for Balinese Secondary School Students - Dipa, Putu Sora; Utami, I Gusti Ayu Lokita Purnamika; Made Hery Santosa, (PANYONARA: Journal of English Education, 2022)
As the facilitator of the learning process, the teacher needs to utilize appropriate media for students to help them learn better. Visual media is considered a great help as it provides information more attractively. Thus, this study aimed to develop infographics as an English teaching medium for 8th-grade junior high school students. The subject of this research was the English learning media used by the 8th-grade teacher at SMPN 4 Singaraja. This study was a Design and Development research which consisted of 3 steps of research, namely design, development, and evaluation. The researcher's notes, infographic development blueprints, instrument validation, and expert judgment were used to collect the data. The data were from the researchers' notes, and the infographic development blueprint was described qualitatively. Meanwhile, the score obtained from the instrument validation and the results of the expert judgment were explained quantitatively. The final result indicated that the infographic is very good to be used as an English teaching medium, especially for the 8th grade of junior high school students. Therefore, this research concluded that by developing books containing infographics, English teachers could have another type of visual media to teach all topics in grade 8 by using infographics.